Clinical effects of preemptive intra-articular lidocaine, dexmedetomidine and lidocaine-dexmedetomidine administration in dogs undergoing arthroscopy. (October 2021) - Brioschi, F.A.; Gioeni, D.; Lazzarini, E.; Del Prete, G.; Bronzo, V.; Jacchetti, A.; Carotenuto, A.M.
Highlights: Intra-articular anaesthesia was useful for pain management in canine arthroscopy. Intra-articular dexmedetomidine provided successful intraoperative analgesia. Intraoperative analgesia using intra-articular lidocaine-dexmedetomidine was successful. Intra-articular treatments produced similar postoperative analgesia. Intra-articular lidocaine-dexmedetomidine promoted atrioventricular blocks in dogs. Abstract: This study investigated the perioperative effects of preemptive intra-articular lidocaine (L group), dexmedetomidine (D group) and lidocaine-dexmedetomidine (LD group) in dogs. Physiological variables were intraoperatively recorded at 5 min intervals starting from baseline (5 min before intra-articular injection). If nociception occurred, IV fentanyl was administered. Postoperative pain was assessed using the Short Form-Glasgow Composite Measure Pain Scale. Twenty-four dogs (eight in each group) were included in this prospective, randomized, masked clinical study. In the LD group, systolic arterial pressure significantly increased at T10 ( P = 0.027), T15 ( P = 0.021) and T20 ( P = 0.022), compared with baseline. In the D and LD groups, mean arterial pressure significantly increased at T10 ( P = 0.022; 0.024), T15 ( P = 0.024; 0.09) and T20 ( P = 0.019; 0.021), compared with baseline and diastolic arterial pressure significantly increased at T10 ( P = 0.026; 0.047), T15 ( P = 0.021; 0.023), T20 ( P = 0.011; 0.012) and T25 ( P = 0.019; 0.027), compared with baseline. In the LD group, heart rate significantly decreased at T5 ( P = 0.031), T10 ( P = 0.026) and T15 ( P = 0.034), compared with baseline. Atrioventricular blocks appeared more frequently in the LD group than in L and D groups ( P = 0.002). Group L received more fentanyl than the D and LD groups ( P = 0.03). No differences in postoperative pain score were detected ( P = 0.121). These findings suggested systemic absorption of intra-articular dexmedetomidine. Intra-articular lidocaine-dexmedetomidine was associated with a greater incidence of atrioventricular blocks. Intra-articular dexmedetomidine, alone and combined with lidocaine, provided better intraoperative analgesia than lidocaine in dogs undergoing arthroscopy, although the 12 h postoperative analgesic effect of the three treatments was similar.